Comparative evaluation of dexmedetomidine with tramadol for post spinal anaesthesia shivering: a prospective randomized comparative study - Shivangi Ganjoo; Sharma, Lalit Mohan; Gupta, Raghav (International journal of basic and clinical pharmacology, 2025)
Background: Shivering after spinal anaesthesia is an unpleasant complication that also results in increased oxygen demand. Researchers have looked at various dosages of tramadol to see whether it helps with shivering after spinal anaesthesia. We compared dexmedetomidine with tramadol 1 mg/kg for the management of post-spinal anaesthesia shivering. Methods: We selected 50 patients who developed shivering after subarachnoid block and split them in half; each group had 25 individuals. One group was administered 1mg/kg intravenous tramadol diluted in 100 ml normal saline, while the other group received 0.5 mcg/kg of dexmedetomidine diluted in 100 ml normal saline. Response time, defined as the duration until shivering stopped after drug administration, was the primary outcome measure. Response rate (defined as a complete cessation of shivering within 15 minutes of administering the drug), recurrence of shivering, changes in clinical parameters and pharmacological side effects were considered secondary outcomes. Results: When compared to tramadol (8.91±1.36 minutes), dexmedetomidine (6.74±1.38 minutes) had a considerably shorter response time (p<0.001). Both groups showed a 96% response rate and 8% recurrence of shivering. There was 1 case of hypotension with dexmedetomidine and 2 cases of nausea with tramadol. All patients in group T recorded a sedation level of 1, whereas all patients in group D recorded a sedation score of 2 (p<0.001). Conclusions: Both dexmedetomidine and tramadol are effective in treating post spinal anaesthesia shivering, but the time taken for shivering to stop completely was significantly lesser with dexmedetomidine(0.5 μg/kg)  than with tramadol(1 mg/kg).